Characterisation of a G9P[8] rotavirus strain identified during a gastroenteritis outbreak in Alice Springs, Australia post Rotarix™ vaccine introduction - Donato, C.; Cannan, D.; Bogdanovic-Sakran, N.; Snelling, Thomas; Kirkwood, C. (Elsevier, 2012)
A large rotavirus gastroenteritis outbreak occurred in the Alice Springs region of the Northern Territory, Australia from the 12th of March until the 11th of July 2007. The outbreak occurred five months after the introduction of the Rotarix™ vaccine. Electropherotype and sequence analysis demonstrated that a single G9P[8] strain was responsible for the outbreak and that the strain remained highly conserved during the outbreak period. The outbreak strain contained amino acid changes in regions of the VP7 and NSP4 genes, with known biological function, when compared to previously characterised G9P[8] strains from Australia and other international locations. The recent vaccine introduction was unlikely to have influenced genotype selection in this setting. Importantly, Rotarix™ vaccine was highly effective against the G9P[8] outbreak strain. © 2011 Elsevier Ltd.